Edukasi Pemberian Senam Kaki Untuk Mencegah Ulkus Kaki Pada Penderita Diabetes Melitus Di Posyandu Lansia Sekar Wangi - Muhammad Lukman Hakim; Pristianto, Arif; Rahim, Amalia Faradila (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Diabetes Mellitus (DM) is the most common non-communicable disease (NCD) in the world. This disease is a heterogeneous disease, characterized by high glucose levels. DM is the 4th cause of death in most developing countries. One of the complications of DM is neuropathy, which is reduced sensation in the feet and is often associated with ulcers on the feet. The aim of this community service is to provide information and knowledge about promotive and preventive efforts in dealing with DM. This outreach method is pre-test, education and post-test which is carried out using leaflets and questionnaires containing questions to measure the level of community knowledge. From this counseling, results were obtained through comparison charts between the pre-test and post-test, namely that there was an increase in knowledge from before the education was carried out and after the education about diabetes mellitus and treating foot ulcers using foot exercises. It is hoped that this counseling will continue to have a good impact on participants and can change healthy living behavior for the better.